Respuesta :
x^3 -x + 2x^2 − 2
= x^3 + 2x^2 - x - 2
= x^2(x + 2) - 1(x+2)
= (x + 2)(x^2 - 1)
= (x+2) (x+1)(x-1)
Step 1: x3 − x + 2x2 − 2
Step 2: x3 + 2x2 − x − 2
Step 3: x2(x + 2) − 1(x + 2)
step 4: (x + 2)(x^2 - 1)
step 5: (x+2) (x+1)(x-1)
answer
Step 4: (x^2 − 1)(x + 2); Step 5: (x − 1)(x + 1)(x + 2)
= x^3 + 2x^2 - x - 2
= x^2(x + 2) - 1(x+2)
= (x + 2)(x^2 - 1)
= (x+2) (x+1)(x-1)
Step 1: x3 − x + 2x2 − 2
Step 2: x3 + 2x2 − x − 2
Step 3: x2(x + 2) − 1(x + 2)
step 4: (x + 2)(x^2 - 1)
step 5: (x+2) (x+1)(x-1)
answer
Step 4: (x^2 − 1)(x + 2); Step 5: (x − 1)(x + 1)(x + 2)